Activation of Seniors in Residential Care Facility - Faltová, Barbora; Čermák, Zdeněk; Měsíčková, Kateřina (University of Pardubice, 2018)
Introduction: It has become a common practice to place elderly people in residential care facilities, providing a relatively good standard of living, but seniors often experience isolation from their families and wider social environment. An elderly person may thus feel lonely and useless. Leisure time activation reduces the negative effects of ageing, gives a greater sense of satisfaction and helps the clients eliminate their possible social isolation. Aim: To find out how a selected senior care home applies activation approaches when working with their clients. Method: Quantitative method was selected for the survey, utilizing a self-designed questionnaire as the research survey tool. The survey took place from early December 2016 to late January 2017. Descriptive statistics was used for evaluating the data. Results: The care facility of interest applies activation approaches to achieve their clients’ satisfaction. A prevailing portion of the clients is not bored in the facility and regularly participates in activation work. Seniors mostly dedicate themselves to fitness training, memory training and musical activities. They prefer group activities. The respondents see minor weaknesses in the limited range of offered activities, which could be extended to cooking, baking and animal therapy. Conclusion: Although respondents have slight reservations to the practice of activation programs at the residential care facility, they are largely satisfied. All respondents are aware of the support provided by the staff. Involving volunteers might help extend and improve the range of activation programs, or integrating seniors into the community life.
Keywords: activation; leisure activities; senior; senior care home